Pengaruh Karakteristik Individu dan Karakteristik Sistem terhadap Niat untuk Menggunakan Teknologi Internet (Studi pada Dosen Universitas Negeri Padang) - Rahmiati - (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2012)
The objective of this research was to investigates the effect of a set of individual characteristics (i.e., computer self efficacy, knowledge of search domain, and Internet experience) and system characteristics (i.e., complexity, relevance, and relative advantage) on intention to use Internet by using the Technology Acceptance Model (TAM) as a basic theory. Questionnaire survey method was used to collect primary data. Statistical analysis methods and Partial Least Square were used to data analyse. Based on a sample of 181 lecturers in Universitas Negeri Padang, the survey result shows that the intention to use Internet influenced by system characteristics through perceived usefulness. Specifically, lecturers largely anchoring their acceptance decisions in the usefulness of the technology rather than in its ease of use. When making decisions to accept a technology, lecturers expressed considerable concerns about the relevance and the relative advantage of the technology on their activities. While individual characteristic variables i.e. computer self efficacy and Internet experience as like as system characteristic variable that is complexity are important determinants of perceived ease of use, they do not affect the lecturer’s intention to use Internet.